2021
DOI: 10.1093/eurheartj/ehab449
|View full text |Cite
|
Sign up to set email alerts
|

Post-stenting fractional flow reserve vs coronary angiography for optimization of percutaneous coronary intervention (TARGET-FFR)

Abstract: Aims  A fractional flow reserve (FFR) value ≥0.90 after percutaneous coronary intervention (PCI) is associated with a reduced risk of adverse cardiovascular events. TARGET-FFR is an investigator-initiated, single-centre, randomized controlled trial to determine the feasibility and efficacy of a post-PCI FFR-guided optimization strategy vs. standard coronary angiography in achieving final post-PCI FFR values ≥0.90. Methods and results  … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 33 publications
(28 reference statements)
2
71
0
6
Order By: Relevance
“…Another group used the hyperemic pullback to detect native focal lesions within the 20 mm segment or the intra-stent gradient by the definition of an FFR increase of ≥0.05 on the pullback curve. However, in that study among patients undergoing successful PCI, a physiology-guided incremental optimization strategy failed to improve the proportion of patients with an optimal result of FFR ≥ 0.9 ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another group used the hyperemic pullback to detect native focal lesions within the 20 mm segment or the intra-stent gradient by the definition of an FFR increase of ≥0.05 on the pullback curve. However, in that study among patients undergoing successful PCI, a physiology-guided incremental optimization strategy failed to improve the proportion of patients with an optimal result of FFR ≥ 0.9 ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“… 30–33 Post-PCI FFR-values are influenced by various factors, such as diffuse CAD without focal lesions, the presence of residual lesions unsuitable for PCI, an initial narrow or short stent trajectory, stent malposition or suboptimal expansion, edge dissection and plaque protrusion. 30 , 31 , 33 Additionally, improved coronary flow after PCI might show other stenoses in the same coronary artery to be functionally significant as well, especially more distal lesions. 31 …”
Section: Practical Aspects and Patient Selectionmentioning
confidence: 99%
“… 30–33 Limited evidence is available, whereas the only randomized controlled trial showed no significant difference in outcomes between physiology-guided and FFR-guided assessment of PCI-results. 33 …”
Section: Practical Aspects and Patient Selectionmentioning
confidence: 99%
“…For the adoption of the PPG, a mandatory requirement is an acceptable test/retest reliability. While the usefulness of an intracoronary pullback maneuver is increasingly recognized, there is no data on the accuracy and reproducibility of PPG derived from manual FFR pullbacks 5 …”
Section: Introductionmentioning
confidence: 99%
“…While the usefulness of an intracoronary pullback maneuver is increasingly recognized, there is no data on the accuracy and reproducibility of PPG derived from manual FFR pullbacks. 5 The objectives of the current study are (1) to validate the PPG calculation derived from manual FFR pullbacks with motorized FFR pullbacks as a reference, and (2) to assess the intra-and interoperator reproducibility of the PPG derived from manual FFR pullbacks.…”
Section: Introductionmentioning
confidence: 99%